2016
DOI: 10.1371/journal.pone.0164457
|View full text |Cite
|
Sign up to set email alerts
|

An Abbreviated Protocol for In Vitro Generation of Functional Human Embryonic Stem Cell-Derived Beta-Like Cells

Abstract: The ability to yield glucose-responsive pancreatic beta-cells from human pluripotent stem cells in vitro will facilitate the development of the cell replacement therapies for the treatment of Type 1 Diabetes. Here, through the sequential in vitro targeting of selected signaling pathways, we have developed an abbreviated five-stage protocol (25–30 days) to generate human Embryonic Stem Cell-Derived Beta-like Cells (ES-DBCs). We showed that Geltrex, as an extracellular matrix, could support the generation of ES-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The protocols for quantitative and digital droplet PCR (ddPCR) have been previously described (28,29). The comparative cycle threshold (2 2DDCt ) method was applied to calculate the relative expression of target gene in each sample, relative to control in the quantitative PCR.…”
Section: Quantitative and Digital Droplet Pcrmentioning
confidence: 99%
“…The protocols for quantitative and digital droplet PCR (ddPCR) have been previously described (28,29). The comparative cycle threshold (2 2DDCt ) method was applied to calculate the relative expression of target gene in each sample, relative to control in the quantitative PCR.…”
Section: Quantitative and Digital Droplet Pcrmentioning
confidence: 99%
“…These data imply that while promoting cell proliferation, the Notch pathway also helps keep endocrine cells at an immature state during development. Interestingly, γ-secretase inhibitors, by blocking the Notch pathway, have been recently introduced into several protocols designed for in vitro generation of functional β cells from human pluripotent stem cell, applied at the last stages of the in vitro culture to promote β cell maturation (Pagliuca et al 2014;Rezania et al 2014;Massumi et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of stage 4, cells express NGN3 and NKX6.1 genes. These cells persist expression of PDX1 and indicate high expression levels of FOXA2, HNF4, GATA4, ISL1 , and NeuroD1 markers as well (Massumi et al., ; Rajaei et al., ). In the last stage, about 50% of the cells express C‐Peptide and few express Somatostatin.…”
Section: Commentarymentioning
confidence: 99%
“…The glucose‐stimulated insulin secretion assay as static and dynamic demonstrated the responsiveness of the GRPβ‐L cells to the glucose concentration by increasing the insulin secretion. We showed that the secretion of the insulin is regulated by an increase in the intracellular Calcium (Massumi et al., )…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation